Hospital-Acquired Infection in Pediatric Subjects With Congenital Heart Disease Postcardiotomy Supported on Extracorporeal Membrane Oxygenation*. Issue 11 (November 2020) - Herrup, Elizabeth A.; Yuerek, Mahsun; Griffis, Heather M.; Connelly, James T.; Thiagarajan, Ravi; Rycus, Peter; Blinder, Joshua J.
Abstract : Objective: To determine prevalence of and risk factors for infection in pediatric subjects with congenital heart disease status postcardiotomy supported on extracorporeal membrane oxygenation, as well as outcomes of these subjects. Design: Retrospective cohort from the Extracorporeal Life Support Organization. Setting: U.S. and international medical centers providing care to children with congenital heart disease status postcardiotomy. Patients: Critically ill pediatric subjects less than 8 years old admitted to medical centers between January 1, 2013, and December 31, 2015, who underwent cardiac surgery for congenital heart disease and required extracorporeal membrane oxygenation support within the first 14 postoperative days. Subjects were excluded if they underwent orthotopic heart transplantation, required preoperative extracorporeal membrane oxygenation, and had more than one postoperative extracorporeal membrane oxygenation run. Interventions: None. Measurements and Main Results: A total of 1, 314 extracorporeal membrane oxygenation subject encounters in the Extracorporeal Life Support Organization registry met inclusion criteria. Neonates comprised 53% ( n = 696) of the cohort, whereas infants made up 33% ( n = 435). Of the 994 subjects with Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery categorizable surgery, 33% ( n = 325) were in Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery category 4 and 23% ( n = 231) in Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery category 5. While on extracorporeal membrane oxygenation, 229 subjects (17%) acquired one or more extracorporeal membrane oxygenation–related infections, which represents an occurrence rate of 67 infections per 1, 000 extracorporeal membrane oxygenation days. Gram-negative (62%) and Gram-positive (42%) infections occurred most commonly. Forty percent had positive blood cultures. Infants and children were at higher infection risk compared with neonatal subjects; subjects undergoing less complex surgery had higher infection rates. Unadjusted survival to hospital discharge was lower in infected subjects compared with noninfected subjects (43% vs 51%; p = 0.01). After adjusting for confounders via propensity matching, we identified no significant mortality difference between infected and noninfected subjects. Conclusions: Neonatal and pediatric subjects in this study have a high rate of acquired infection. Infants and children were at higher infection risk compared with neonatal subjects. There was not, however, a significant association between extracorporeal membrane oxygenation–related infection and survival to hospital discharge after propensity matching. Abstract : Supplemental Digital Content is available in the text.